Relationship quality among younger and middle-aged siblings: the role of childhood family arrangements - Tanskanen A.O; Danielsbacka M.; Rotkirch A. (Suomen akatemia, 2022)
Sibling relationships are the social bonds with longest duration across the life course. Using a large and population-based data of younger and middle-aged Finns, we test how childhood co-residence duration and maternal perinatal association (MPA) correlate with contact frequency, emotional closeness and provision of help between adult siblings. Employing sibling fixed-effect models we find that duration of co-residence in childhood and MPA are indeed associated with increased relationship quality in all three measures. Provided MPA, sibling relationship quality is high independent of co-residence length, but in the absence of MPA, increased co-residence duration is associated with better relationship quality. Co-residence duration is more strongly associated with provision of help in same-gender than opposite-gender sibling dyads. Full siblings report better relationship quality than half siblings do, although the co-residence duration mediates the effect of genetic relatedness in emotional closeness between full and maternal half siblings and in provision of help between full and paternal half siblings. Moreover, MPA serves as a mediator in the case of contact frequency and emotional closeness between full and maternal half siblings. These findings are discussed with reference to key theories of kin detection.